Chameleon Metals: Autonomous Nano‐Texturing and Composition Inversion on Liquid Metals Surfaces. Issue 1 (2nd December 2019) - Martin, Andrew; Kiarie, Winnie; Chang, Boyce; Thuo, Martin
Abstract: Studies on passivating oxides on liquid metals are challenging, in part, due to plasticity, entropic, and technological limitations. In alloys, compositional complexity in the passivating oxide(s) and underlying metal interface exacerbates these challenges. This nanoscale complexity, however, offers an opportunity to engineer the surface of the liquid metal under felicitous choice of processing conditions. We inferred that difference in reactivity, coupled with inherent interface ordering, presages exploitable order and selectivity to autonomously present compositionally biased oxides on the surface of these metals. Besides compositional differences, sequential release of biased (enriched) components, via fractal‐like paths, allows for patterned layered surface structures. We, therefore, present a simple thermal‐oxidative compositional inversion (TOCI) method to introduce fractal‐like structures on the surface of these metals in a controlled (tier, composition, and structure) manner by exploiting underlying stochastic fracturing process. Using a ternary alloy, a three‐tiered (in structure and composition) surface structure is demonstrated. Abstract : Chameleon metals : Metal passivating oxide layer is a complex pseudo‐equilibrium system with a plethora of undiscovered features. Here, the complexity of this thin oxide layer is exploited to engineer surface design and structure, resulting in the formation of compositionally inverted surface features and nano‐scale fractal‐like designs.